The Quality of Medical Advice in Low-Income Countries - Das, Jishnu (2012)
This paper documents the quality of medical advice in low-income countries. Our evidence on health care quality in low-income countries is drawn primarily from studies in four countries: Tanzania, India, Indonesia, and Paraguay. We provide an overview of recent work that uses two broad approaches: medical vignettes (in which medical providers are presented with hypothetical cases and their responses are compared to a checklist of essential procedures) and direct observation of the doctor--patient interaction These two approaches have proved quite informative. For example, doctors in Tanzania complete less than a quarter of the essential checklist for patients with classic symptoms of malaria, a disease that kills 63,000-96,000 Tanzanians each year. A public-sector doctor in India asks one (and only one) question in the average interaction: "What's wrong with you?" We present systematic evidence in this paper to show that these isolated facts represent common patterns. We find that the quality of care in low-income countries as measured by what doctors know is very low, and that the problem of low competence is compounded due to low effort--doctors provide lower standards of care for their patients than they know how to provide. We discuss how the properties and correlates of measures based on vignettes and observation may be used to evaluate policy changes. Finally, we outline the agenda in terms of further research and measurement.